The influence of Teaching Factory (TEFA) implementation and work readiness on vocational high school students' future job perspectives - Imran Imran; Marji Marji; Hary Suswanto; Basanta Prasad Adhikari (Jurnal Pendidikan Vokasi, 2024)
Graduates who are superior, competitive, and ready to work are the goals of vocational education. The purpose of this research is to determine the impact of Teaching Factory (TEFA) implementation with the Context, Input, Process, and Product (CIPP) evaluation model and student work readiness on the Occupational Future Time Perspective (OFTP). Indeed, nowadays, professional/vocational graduates must be ready to enter the industrial world after graduation. This research involved 456 respondents of Vocational High School (VHS) students in South Sulawesi, Indonesia, who were determined using a proportional random sampling technique. This type of research is descriptive quantitative with data analysis using SEM AMOS. The results showed that there was a significant influence between the implementation of TEFA and the level of work readiness up to 57%, while the actual contribution of teaching and work readiness factors to future employment time was 80.7%. Overall, the results show that the implementation of TEFA has successfully helped students become more independent and ready to face the competitive world of work. Although 19.3 factors still influence work readiness and prospects, the research results do not change much. Therefore, the application of a teaching factory in the learning process is highly recommended for teachers and students in vocational schools. The implementation can be adjusted to the learning conditions and resources available in VHS. This research contributes as a source of reference in future studies related to improving practical learning and developing students' entrepreneurial skills.